New Empirics of monetary policy dynamics: evidence from the CFA franc zones - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Purpose A major lesson of the EMU crisis is that serious disequilibria in a monetary union result from arrangements not designed to be robust to a variety of shocks. With the specter of this crisis looming substantially and scarring existing monetary zones, the present study has complemented existing literature by analyzing the effects of monetary policy on economic activity (output and prices) in the CEMAC and UEMOA CFA franc zones. Design/methodology/approach VARs within the frameworks of VECMs and Granger causality models are used to estimate the long-run and short-run effects respectively. Impulse response functions are further used to assess the tendencies of significant Granger causality findings. A battery of robustness checks are also employed to ensure consistency in the specifications and results. Findings Hypothesis 1: Monetary policy variables affect prices in the long-run but not in the short-run in the CFA zones (Broadly untrue). This invalidity is more pronounced in CEMAC (relative to all monetary policy variables) than in UEMOA (with regard to financial dynamics of activity and size). Hypothesis 2: Monetary policy variables influence output in the short-term but not in the long-run in the CFA zones. Firstly, the absence of co-integration among real output and the monetary policy variables in both zones confirm the long-term dimension of the hypothesis on the neutrality of money. The validity of its short-run dimension is more relevant in the UEMOA zone (with the exception of overall money supply) than in the CEMAC zone (in which only financial dynamics of 'financial system efficiency' and financial activity support the hypothesis). Practical Implications (1) Compared to the CEMAC region, the UEMOA zone's monetary authority has more policy instruments for offsetting output shocks but fewer instruments for the management of short-run inflation. (2) The CEMAC region is more inclined to non-traditional policy regimes while the UEMOA zone dances more to the tune of traditional discretionary monetary policy arrangements. A wide range of policy implications are discussed. Inter alia: implications for the long-run neutrality of money and business cycles; implications for credit expansions and inflationary tendencies; implications of the findings to the ongoing debate; country-specific implications and measures of fighting surplus liquidity. Originality/value By using a plethora of hitherto unemployed financial dynamics (that broadly reflect money supply), we have provided a significant contribution to the empirics of monetary policy. The conclusion of the analysis is a valuable contribution to the scholarly and policy debate on how money matters as an instrument of economic activity in developing countries and monetary unions.
Keywords: E51; E52; E58; E59; O55; 330; Monetary Policy; Banking; Inflation; Output effects; Africa